2019
DOI: 10.29252/jafm.12.03.29476
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of a Turbulent Multiple Jets Issued from Lobed Diffusers

Abstract: A combined experimental and computational study of a turbulent multiple jet from lobed diffusers is performed. The main interest of these multiple lobed jets is to come up with the best configuration that improves the thermal and dynamic homogenization in air diffusion units that can be used for ventilation, heating and air conditioning of residential premises. Herein, the configuration of a central lobed jet surrounded by six equidistant peripheral lobed jets has been investigated. On the experimental level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The ventilation system in vehicles plays a critical role in providing a steady supply of fresh air and removing the pollutants from the ambient air by diluting it. High-induction air diffusers with lobed orifices are a promising solution for improving IEQ in vehicles [27]. The same conclusion was pointed out in [28], where these air diffusers supply fresh air into the ventilated enclosure and mix it with the existing ambient air, thereby lowering pollutant levels and enhancing the overall IEQ.…”
Section: Introductionmentioning
confidence: 65%
“…The ventilation system in vehicles plays a critical role in providing a steady supply of fresh air and removing the pollutants from the ambient air by diluting it. High-induction air diffusers with lobed orifices are a promising solution for improving IEQ in vehicles [27]. The same conclusion was pointed out in [28], where these air diffusers supply fresh air into the ventilated enclosure and mix it with the existing ambient air, thereby lowering pollutant levels and enhancing the overall IEQ.…”
Section: Introductionmentioning
confidence: 65%
“…Some scholars have proved the practicability of this model in numerical simulations. 38,39 In this study, the Schiller-Naumann model is chosen for the drag force between the gas and liquid phases, which is the earliest and most famous among the commonly used drag force models. The drag force coefficient between the gas and liquid phases is calculated by dividing the relative bubble Reynolds number into two ranges, as done by Niu et al, 40 Feng et al, 20 and Liu et al 21 in their numerical simulations and experiments.…”
Section: Numerical Methods and Settingmentioning
confidence: 99%
“…The SST k ‐omega turbulence model is used in the liquid phase. Medaouar et al 39 pointed that the SST k ‐omega model considers the transfer effect of turbulent shear stress at the wall, and can better predict the flow separation near the wall and the separation region in fluid mechanical equipment, especially in multiphase mixing pumps. The dispersed‐phase zero‐equation model is used for the gas phase.…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the entrainment rate is due to the asymmetric shape of the nozzle and the strong convection of the turbulent structures induced by the lobes. Medaouar et al [8] performed a combined experimental and computational study of a central lobed jet surrounded by six equidistant peripheral lobed jets, and found that the interaction between the jets leads to velocity and temperature redistribution in the mixed zone. while allowing the propagation of the resulting jet.…”
Section: Introductionmentioning
confidence: 99%